A Pragmatic Analysis of Communication Strategies Employed by English Educational Content Creator on TikTok - Prastagha, Mochammad Yuda; Aisyah, Siti; Sabat, Yuliyanto (Journal of English Development, 2026)
This study aims at the use of pragmatic communication techniques in TikTok English language learning content, with a particular emphasis on the well-known creator @nathan_suparman as subject. The theory used in this research is based from George Yule's pragmatic theories, the study examines 42 utterances from four educational content using a qualitative descriptive method and content analysis to determine the employment of speech acts, politeness strategies, and conversational implicature. Results show Representative speech acts dominate the content to explain concepts and grammatical rules in line with the educational goal. Bald-on-record politeness is the most frequent strategy, reflecting TikTok’s straightforward, light-hearted, and fast-paced style. Contextual wordplay, miscommunication, and humor often generate particularized conversational implicature, enhancing audience engagement and cognitive processing. This contributes pedagogical model for digital language and acquisition study comes to the conclusion that a successful and captivating is produced by the deliberate integration of audience-oriented Speech act, Politeness and implicatures, contextual comedy, and direct instruction, for educators and content producers looking to maximize English language instruction in social media settings, these pragmatical strategies not only support comprehension but also maintain learner motivation to learning with the social media.